Regulatory Actions of Estrogen Receptor Signaling in the Cardiovascular System - Ueda, Kazutaka; Adachi, Yusuke; Liu, Pangyen; Fukuma, Nobuaki; Takimoto, Eiki (Frontiers in Endocrinology, 2020)
Premenopausal females have a lower incidence of death from cardiovascular disease (CVD) than male counterparts., supporting the notion that estrogen is protective against the development and progression of CVD. Although large-scale randomized trials of postmenopausal hormone replacement therapy failed to show cardiovascular benefits, recent ELITE study demonstrated anti-atherosclerotic benefits of exogenous estrogen depending on the initiation timing of the therapy. These results have urged us to better understand the mechanisms for actions of estrogens on CVD. Here, we review experimental and human studies, highlighting the emerging role of estrogen’s non-nuclear actions linking to NO-cGMP signaling pathways.